2015
DOI: 10.1002/pon.3836
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer survivors' perceived medical communication competence and satisfaction with care at the end of treatment

Abstract: In order to enhance supportive care for BCS, younger BCS should be provided with more time to address all their concerns and older BCS should be encouraged to express their specific desires for information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 44 publications
1
18
0
1
Order By: Relevance
“…It has previously been recognised that transition at the end of active treatment into survivorship for AYA is complex and requires support through a multitude of tailored services (CanTeen, ). Findings of this review have shown that AYA experience difficulty in accessing the survivorship support they need, wanting more time for consultations with doctors, and more targeted, age‐appropriate and accessible support and information compared to older adults (Brédart et al, ; Shen et al, ). Adolescents and young adults wanted honest communication in these early stages post‐treatment about what the long‐term implications of their cancer treatment could be (Decker et al, ; May et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has previously been recognised that transition at the end of active treatment into survivorship for AYA is complex and requires support through a multitude of tailored services (CanTeen, ). Findings of this review have shown that AYA experience difficulty in accessing the survivorship support they need, wanting more time for consultations with doctors, and more targeted, age‐appropriate and accessible support and information compared to older adults (Brédart et al, ; Shen et al, ). Adolescents and young adults wanted honest communication in these early stages post‐treatment about what the long‐term implications of their cancer treatment could be (Decker et al, ; May et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this rapid review demonstrate the overarching issues experienced by AYA with cancer at the end of treatment, highlighting a paucity of research exploring the particular issues experienced by AYA with different diagnoses. Where research in older adults tends to focus on single, high‐prevalence diagnoses, such as breast cancer (Brédart et al, ; Costa‐Requena, Rodríguez, Fernández, Palomera, & Gil, ; Jones et al, ), AYA research tends to look at the patient population as a whole, without splitting it into diagnostic groups, likely due to the small numbers when looking at tumour types. Nonetheless, it would be useful and important to determine whether the issues which arise at the end of treatment vary according to diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reasons for the unmet information needs among YWBC might include physicians' time limitations, non-identification of particular concerns and lack of training in communication skills. Younger patients require sufficient time to address all of their concerns, and low physician availability correlates with higher information needs in these patients (Bredart, Kop, Fiszer, Sigal-Zafrani, & Dolbeault, 2015). Lack of time during medical appointments limits the exchange of information between patients and physicians, especially at the first medical visit.…”
Section: Several Patients Mentioned Not Being Informed In Detail Aboutmentioning
confidence: 99%
“…Studies have shown that patients' problems frequently persist even long after treatment has been completed [4][5][6][7], and that physical, family/social, and emotional problems are associated with psychological distress [8][9][10]; however, several studies have shown that patients are often reluctant to disclose psychosocial problems and needs to health professionals [1,[11][12][13] even though these needs are described by cancer patients as unmet [3,4,14]. Problems experienced, unmet needs, and distress may affect patients' satisfaction with care, adherence to treatment, and quality of life [2,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%